2021
DOI: 10.1016/j.omtn.2020.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced muscle atrophy via PPARγ suppression is mediated by miR-29b

Abstract: The activation of the renin-angiotensin system (RAS) induced by increased angiotensin II (AngII) levels has been implicated in muscle atrophy, which is involved in the pathogenesis of congestive heart failure. Although peroxisome proliferatoractivated receptor gamma (PPARg) activation can suppress RAS, the exact role of PPARg in AngII-induced muscle atrophy is unclear. Here we identified PPARg as a negative regulator of miR-29b, a microRNA that is able to promote multiple types of muscle atrophy. Suppression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…miRNA can inhibit the expression of target genes in two ways by organizing mRNA translation or causing it to be explained by RISC [ 22 , 23 ]. In previous studies, it was found that miRNAs are involved in various regulatory pathways in skeletal muscle [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. For example, miR-696 has been confirmed to be a physical-activity-dependent miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA can inhibit the expression of target genes in two ways by organizing mRNA translation or causing it to be explained by RISC [ 22 , 23 ]. In previous studies, it was found that miRNAs are involved in various regulatory pathways in skeletal muscle [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. For example, miR-696 has been confirmed to be a physical-activity-dependent miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase reporter assays in AC16 cell were performed as described previously. 12 For analysis the target genes of miR-30d, the sequences and mutated sequences of 3’UTR of MAP4K4 and GRP78 were cloned into PGL3-basic vector. Luciferase reporter assays in HEK239 cell and H9C2 cell were performed as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Luciferase reporter assays in HEK239 cell and H9C2 cell were performed as described previously. 12 The sequences used in this study were listed in Table S4.…”
Section: Methodsmentioning
confidence: 99%
“… 5 miR-29b has been showed to promote many types of muscle atrophy including heart failure-induced muscle wasting via regulating target genes IGF-1, PI3K, and YY1. 50 , 51 Peroxisome proliferator activated receptor gamma (PPARγ) was found to inhibit AngII-induced muscle atrophy and improve muscle function by targeting and downregulating miR-29b; 51 , 52 similarly, inhibition of miR-29b by the CRISPR-Cas9 editing system significantly attenuated AngII-induced muscle atrophy in vivo . 53 It is noteworthy that several muscle-specific miRNAs, including miR-1, miR-133a, miR-133b, miR-208a, and miR-208b, have been found to be involved in the regulation of both cardiac and skeletal muscle functions.…”
Section: Ncrnas In Muscle Atrophy Induced By Heart Failurementioning
confidence: 99%